Implementasi Model Pembelajaran Kolaboratif untuk Meningkatkan Kompetensi Guru Calon dalam Program PPG - Tuti Mutia; Alfi Sahrina; Fatiya Rosyida; Adip Wahyudi; Riska Aprilia; Nita Laura Pratama (Educatio, 2025)
The Teacher Professional Education Program (PPG) has an important role in improving the competency of prospective teachers to meet professional demands. This research aims to analyze the implementation of the collaborative learning (CL) model in improving the competency of Pre-Service Teacher Education students during Field Experience Practices (PPL). The CL model implemented integrates three main approaches: co-teaching, coaching, and consulting, involving students, tutors (GP), and field supervisors (DPL) in one collaborative team. The research method used is descriptive qualitative with a classroom action approach, collecting data through observation, interviews, and questionnaires before and after implementing the model. The research results showed a significant increase in students' pedagogical, personality, professional and social competencies. The implementation of the collaborative model succeeded in increasing the average score of students' pedagogical abilities from 3.08 to 3.86. Additionally, 80% of students reported increased self-confidence and interpersonal skills. In terms of classroom management, 80% of students were able to create an active learning atmosphere after the program. Improvements in social skills were also visible, with the average score increasing from 3.5 to 4.2, reflecting students' ability to share ideas and collaborate. Collaborative learning not only improves academic skills, but also supports the development of teacher candidates' personality and social skills, preparing them for challenges in the dynamic world of education